Jom ghaso makane Kelate / Wan Anisha Wan Mohammad and Syarifah Adilah Mohamed Yusoff - Wan Mohammad, Wan Anisha; Mohamed Yusoff, Syarifah Adilah (Unit Penerbitan Dan Publisiti JSKM, 2024)
Nasi kabu Etok salai Kabu saghe Nasi dage Tupat sotong Lakse